Hábitos alimenticios y estado nutricional en los estudiantes del Colegio de Bachillerato Fiscomisional Daniel Álvarez Burneo. - Pontón Ramón, Gabriela Katherine (2016)
Adolescence is a stage of accelerated growth with morphological and physiological changes, therefore it is considered a risk period and, therefore it is essential to value nutritionally to identify the most common nutritional problems, Thus this research entitled "Eating habits and nutritional status in high school students “Daniel Alvarez Burneo” of the Loja city during the period February to July 2015 aimed to know the relationship between dietary habits and nutritional status. The study used a design descriptive, cross section.The instruments were a semi-structured survey with closed questions and data collection sheet for recording anthropometric measurements. The sample was 346 students. The results included the occasional consumption of noodles 75.4%, dairy (cheese 54%, milk 45% and 32% yogurt), butter 82% and fish 84%; in daily food intake we have to fruits and rice 34.68% 68.5%; snacks consumption of 77.46%, sugary drinks 77.46% and fast foods of 67.14%, adolescents consume 3 to 4 glasses of water a day at 43.35%. With regard to meals 82% consume breakfast daily and 57.51% of respondents occasionally feed at the same time. The 60.16% of students with healthy habits has normal body mass index and 88.89% of respondents are overweight unhealthy habits. For this reason it was concluded that adolescent girls practice unhealthy habits that affect body mass index. Keywords: food, nutritional status, habits, adolescence.